2017
DOI: 10.1371/journal.pone.0174062
|View full text |Cite|
|
Sign up to set email alerts
|

Dual-targeting of Arabidopsis DMP1 isoforms to the tonoplast and the plasma membrane

Abstract: The reports of dual-targeted proteins in plants have steadily increased over the past years. The vast majority of these proteins are soluble proteins distributed between compartments of the non-secretory pathway, predominantly chloroplasts and mitochondria. In contrast, dual-targeted transmembrane proteins, especially of the secretory pathway, are rare and the mechanisms leading to their differential targeting remain largely unknown. Here, we report dual-targeting of the Arabidopsis DUF679 Membrane Protein 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…Considering the default localization of DMP9 in sperm cells, it is suggested that DMP9 on the sperm surface functions prior to or simultaneously with GCS1/HAP2 and GEX2. A recent study reported that two isoforms of DMP1 (DMP1.1 and 1.2) showed different destinations, the tonoplast (TP) and the plasma membrane (PM), within a cell (Kasaras and Kunze, 2017). The fact that DMP9 has no signal sequence at the N terminus and shows no TP localization in onion epidermal cells also strongly suggests that DMP9 localization is restricted to the plasma membrane in sperm cells.…”
Section: Results and Discussion Identification And Characterization Omentioning
confidence: 99%
“…Considering the default localization of DMP9 in sperm cells, it is suggested that DMP9 on the sperm surface functions prior to or simultaneously with GCS1/HAP2 and GEX2. A recent study reported that two isoforms of DMP1 (DMP1.1 and 1.2) showed different destinations, the tonoplast (TP) and the plasma membrane (PM), within a cell (Kasaras and Kunze, 2017). The fact that DMP9 has no signal sequence at the N terminus and shows no TP localization in onion epidermal cells also strongly suggests that DMP9 localization is restricted to the plasma membrane in sperm cells.…”
Section: Results and Discussion Identification And Characterization Omentioning
confidence: 99%
“…Subcellular localization of ClAAP3 and ClAAP6 were performed by using translational fusions with GFP in Nicotiana benthamiana leaves. Each AAP gene was translationally fused with GFP on either N’- and C’- side, since previous studies have shown that depending on the location of targeting motifs, both C or N terminal fusions can mislocalize [26,27]. The results showed that both fusions localize to the structure resembling perinuclear ER membrane and the periphery of the cells, presumably the plasma membrane (Figure 6a,f,k,p).…”
Section: Resultsmentioning
confidence: 88%
“…PDIs rearrange disulfide bridges in ER‐associated proteins to restore protein structure (Nawkar et al, 2018). DMP5 of the plant DMP1 family is part of the secretory pathway and is targeted to the plasma membrane and tonoplast (Kasaras & Kunze 2017). PDI and DMP5 were differentially regulated early on, likely to maintain ER homeostasis.…”
Section: Resultsmentioning
confidence: 99%